Effects of Binahong (Anredera Cordifolia) Leaf Ethanol Extracts on Blood Glucose Levels and Pancreas Histopathology in Hyperglycemic Rats - Sri Wahjuni (Journal of Global Pharma Technology, 2016)
Background: The use of binahong leaf has been carried out for medical purposes for centuries. Severalstudies have shown that binahong contain alkaloids, saponins, tannins, glycosides, and terpenes,which can be known to have effects to reduce blood sugar levels. Objective: This study to determinethe effect of binahong leaf ethanol extract in reducing blood glucose and histopathological change inhyperglycemic rats. Method: This study was an experimental study using Wistar rats that weredivided into five groups. The normal group was given with distilled water (P0), the positive controlgroup received glibenclamide (P1), and intervention group was given orally binahong leaf extract ofethanol with a dose of 10mg/kg (P2), 15 mg/kg (P3) and 20 mg/kg (P4). Blood sugar level wasevaluated from the initial day of measurement to two weeks. Pancreas tissue was obtained toevaluate the histopathological change. Results: Mean blood sugar level in each group respectively94.28±6.19 mg/dL, 133.61±47.05 mg/dL, 117.56±26.73 mg/dL, 124.77±37.05 mg/dL, and 136.57±47.55mg/dL. The result of Kruskal-Wallis test was p=0.011. Multiple comparison test showed significantresult between P4 with P0 (p=0.011). Conclusion: Binahong leaf ethanol extract with a dose of 20mg/kg significantly reduce blood glucose level in the hyperglycemic rat.Keywords: Binahong, Anredera cordifolia, Blood glucose, Hyperglycemic rat.